Host-parasite interactions and trypanosome morphogenesis: a flagellar pocketful of goodies. - Gull, K (2003)
Trypanosomes are characterised by the possession of a single flagellum and a subpellicular microtubule cytoskeleton. The flagellum is more than an organelle for motility; its position and polarity along with the sub-pellicular cytoskeleton enables the morphogenesis of a distinct flagellar pocket and the flagellar basal body is responsible for positioning and segregating the kinetoplast--the mitochondrial genome. Recent work has highlighted the molecules and morphogenesis of these cytoskeletal/flagellum structures and how dynamic events, occurring in the flagellar pocket and kinetoplast, are critical for host-parasite interactions.